Hydrogel Microcapsules: Hydrogel Microcapsules with a Thin Oil Layer: Smart Triggered Release via Diverse Stimuli (Adv. Funct. Mater. 18/2021). (3rd May 2021) - Jeong, Hye‐Seon; Kim, Eunseo; Nam, Changwoo; Choi, Yoon; Lee, You‐Jeong; Weitz, David A.; Lee, Hyomin; Choi, Chang‐Hyung
Abstract : In article number 2009553, Hyomin Lee, Chang‐Hyung Choi, and co‐workers present hydrogel microcapsules with an intermediate thin oil layer that enable the smart release of a broad range of hydrophilic cargoes triggered via diverse stimuli. The osmotic pressure and the overall stiffness of the hydrogel microcapsules can be fine‐tuned to control the onset time of release and the release behavior of multi‐cargo encapsulated hydrogel microcapsules to be either simultaneous or selective.